2011
DOI: 10.4081/reumatismo.2006.268
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular etanercept treatment for severe diffuse pigmented villonodular knee synovitis

Abstract: Pigmented villonodular synovitis (PVNS) is a rare pre-malignant disease that require aggressive treatment as surgical synovectomy, eventually followed by radiosynovectomy. Nevertheless, the disease often reoccurs after these treatments. To determine the safety and efficacy of intra-articular (IA) TNF-a blockade with etanercept (ETN), before extended arthroscopic synovectomy, in severe PVNS of the knee, two patients, (a 26-year-old man with B27+ undifferentiated spondylarthropathy and a 32-year-old femal with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Recent studies showed that anti-inflammatory therapy with anti-TNF biologics (infliximab systemic and etanercept intra-articular) and anticancer imatinib (tyrosine-kinase inhibitor of signaling cascade) may be helpful in management of PVNS [10,13,14]. Large amounts of TNF-alpha were found in PVNS similarly to rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that anti-inflammatory therapy with anti-TNF biologics (infliximab systemic and etanercept intra-articular) and anticancer imatinib (tyrosine-kinase inhibitor of signaling cascade) may be helpful in management of PVNS [10,13,14]. Large amounts of TNF-alpha were found in PVNS similarly to rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 99%
“…Synovial hyperplasia in PVNS might be due to upregulation of synoviocyte proliferation as represented by activation of telomerase, which is evident in the majority of tumor cell lines [15]. That is why the treatment such as with TNF-alpha blockade did not reduce synovial tumor mass as measured by MRI but alleviated and stabilized synovial inflammation and joint effusion [13,14]. However, treatment with imatinib showed MRI decrease in size of lesions in 50% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a marked reduction in macrophages and TNF-a expression in the synovium was found. Fiocco et al reported two patients with recurrent disease of the knee who benefited from the TNF-a blocker etanercept [63]. Knee function and disease activity improved, which was confirmed by regression of knee joint synovial proliferation.…”
Section: Immunotherapymentioning
confidence: 92%
“…Some research uses anti-TNF-a as a local or general treatment in patients with relapsing PVNS, with relatively good results [30,63,64]. Kroot reported a patient with recurrent PVNS of the knee, which clinically improved after TNF-a blockade [30].…”
Section: Immunotherapymentioning
confidence: 99%
“…Fiocco at al. [14] described 2 patients with recurrent PVNS, successfully treated with intra-articular etanercept injections. The patients regained full range of mo-Reumatologia 2021; 59/5 tion in the treated joints, and US evaluation revealed reduction of thickness of the synovial tissue.…”
mentioning
confidence: 99%